Hyperoxia Provokes Time- and Dose-Dependent Gut Injury and Endotoxemia and Alters Gut Microbiome and Transcriptome in Mice - Li, Yunhang; Tao, Yuanfa; Xu, Jingyu; He, Yihuai; Zhang, Wen; Jiang, Zhigang; He, Ying; Liu, Houmei; Chen, Miao; Zhang, Wei; Xing, Zhouxiong (Frontiers in Medicine, 2021)
Background: Oxygen therapy usually exposes patients to hyperoxia, which induces injuries in the lung, the heart, and the brain. The gut and its microbiome play key roles in critical illnesses, but the impact of hyperoxia on the gut and its microbiome remains not very clear. We clarified the time- and dose-dependent effects of hyperoxia on the gut and investigated oxygen-induced gut dysbiosis and explored the underlying mechanism of gut injury by transcriptome analysis. Methods: The C57BL/6 mice were randomly divided into the control group and nine different oxygen groups exposed to hyperoxia with an inspired O2 fraction (FiO2) of 40, 60, and 80% for 24, 72, and 168 h (7 days), respectively. Intestinal histopathological and biochemical analyses were performed to explore the oxygen-induced gut injury and inflammatory response. Another experiment was performed to explore the impact of hyperoxia on the gut microbiome by exposing the mice to hyperoxia (FiO2 80%) for 7 days, with the 16S rRNA sequencing method. We prolonged the exposure (up to 14 days) of the mice to hyperoxia (FiO2 80%), and gut transcriptome analysis and western blotting were carried out to obtain differentially expressed genes (DEGs) and signaling pathways related to innate immunity and cell death. Results: Inhaled oxygen induced time- and dose-dependent gut histopathological impairment characterized by mucosal atrophy (e.g., villus shortening: 80% of FiO2 for 24 h: P = 0.008) and enterocyte death (e.g., apoptosis: 40% of FiO2 for 7 days: P = 0.01). Administered time- and dose-dependent oxygen led to intestinal barrier dysfunction (e.g., endotoxemia: 80% of FiO2 for 72 h: P = 0.002) and potentiated gut inflammation by increasing proinflammatory cytokines [e.g., tumor necrosis factor alpha (TNF-α): 40% of FiO2 for 24 h: P = 0.003)] and reducing anti-inflammatory cytokines [Interleukin 10 (IL-10): 80% of FiO2 for 72 h: P < 0.0001]. Hyperoxia induced gut dysbiosis with an expansion of oxygen-tolerant bacteria (e.g., Enterobacteriaceae). Gut transcriptome analysis identified 1,747 DEGs and 171 signaling pathways and immunoblotting verified TLR-4, NOD-like receptor, and apoptosis signaling pathways were activated in oxygen-induced gut injury. Conclusions: Acute hyperoxia rapidly provokes gut injury in a time- and dose-dependent manner and induces gut dysbiosis, and an innate immune response is involved in an oxygen-induced gut injury.